Predicting Frequency of Treatment Visits in Community-Based Youth Psychotherapy - Brookman-Frazee, Lauren (2008)
The current study examines factors associated with the number of treatment visits attended by a youth and/or family, including sociodemographic variables, youth clinical characteristics and parent/family characteristics at intake, therapist characteristics, and treatment entry characteristics. A total of 57 therapists in two publicly-funded youth mental health clinics and 169 youths and parents from the therapists’ combined caseloads were included in the study. Negative binomial regression was used to examine whether factors within these domains predict the number of treatment visits in this community-based sample. Both therapist and treatment entry characteristics significantly predicted the frequency of treatment visits. Specifically, youth self report of higher symptom severity and stronger parent-youth treatment goal agreement were associated with a higher number of treatment visits. Implications for research and practice are discussed.